Ten tips to harnessing generative AI for high-quality MCQS in medical education assessment - Mohi Eldin Magzoub; Imran Zafar; Fadi Munshi; Fouzia Shersad (Medical Education Online, 2025)
Generating high quality MCQs is time consuming and expensive. Many strategies are applied to produce high quality items including sharing of item banks, training of item writers and automatic item generation (AIG). Generative AI, when used with precision, has proven to reduce significantly both cost and time without compromising quality. Medical educators encounter numerous obstacles when using AI to generate MCQs of good quality. We searched the fast and recent growing medical education literature for articles related to the use of AI in generating high quality MCQs. Additionally, the development of these tips was guided by our own institutional experience.  We created 10 tips for MCQ generation using AI to assist MCQ item writers in both undergraduate and graduate medical education.